URGENSI UU NO 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH DALAM RANGKA MEWUJUDKAN OTONOMI DESA - Jon Asmara, Candra; ', Ermansyah (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Principal focus this Research is study deeper about execution of countryside governance [in]Countryside of Foreland of District of Koto of Kampar of Pate;Upstream of Kampar Sub-Province inorder to realizing countryside autonomy, but practically countryside governance not yet can be realizedeffectively and efficient. Its form [is] countryside governance not yet seen from ability from Countrysideof Foreland of District of Koto of Kampar of Pate;Upstream of Kampar Sub-Province, in managingfinance of countryside and countryside institute, what not yet measure up to the independence in thecountryside governance execution.Implementation from Number Law 32 Year 2004 in realizing countryside governance inCountryside of Countryside of Foreland of District of Koto of Pate;Upstream Kampar, goods have ofcourse get various resistance. As for resistance which researcher find in executing countryside governance[in] Countryside of Countryside of Foreland of District of Koto of Pate;Upstream Kampar is not yet madeavailable of good human resource ability and professional, finance which not yet adequate, availibility ofequipments and facility which still minim and execution of governance management which uncommittbetter. This matter cause its form not yet otoomi countryside, specially [in] Countryside of Countryside ofForeland of District of Koto of Pate;Upstream Kampar.Keyword: Implementation of Policy and Countryside Autonomy